The influence of bird netting on yield and fruit, juice, and wine composition of Vitis vinifera L. - Vinay Pagay; Andrew G. Reynolds; K. Helen Fisher (OENO One, 2013)
Aims: To investigate the impact of semi-permanent bird netting and timing of its application on Cabernet franc grapevine yield components and fruit, juice, and wine composition. Methods and results: Semi-permanent bird netting was installed over Cabernet franc grapevines at various times – post-bloom, bunch closure, and veraison – of the 2004 growing season in the Niagara Peninsula of Canada. At harvest, vine yield components were measured followed by berry and must compositional analysis of soluble solids, pH, titratable acidity (TA), color, and polyphenols. Wines made from these grapes were also analyzed (pH, TA, color, and polyphenols). It was found that installation of bird netting over grapevines had minimal effect on yield components and berry composition regardless of when the nets were installed. Must composition revealed significant decreases in soluble solids, pH, and color as a result of the netting, the least impact being when the nets were applied at post-bloom. Wine composition was similar to the must data with the netted treatments resulting in lower pH, higher TA, and decreased color. Total anthocyanins and polyphenols were slightly reduced as a result of the netting. Conclusions: Minimal impact of bird netting on yield, fruit, must and wine quality is a positive finding since netting is becoming more prevalent in vineyards worldwide due to changing migratory patterns of birds. It is recommended that netting be applied around post-bloom for the ease of application, to minimize shading effects, which could lead to decreased fruit quality, and to maintain yield. Significance and impact of the study: Use of bird netting is becoming more prevalent by grape growers worldwide due to changing migratory patterns of birds that feed on grapes. This study shows that bird netting is not detrimental to yield and fruit and wine quality especially when applied early in the growing season.